Calanus helgolandicus - more than a guest in the north?. (10th December 2022) - Schultz, Mads; Choquet, Marvin; Tverberg, Vigdis; Hoarau, Galice
Abstract: Molecular identification of Calanus helgolandicus has revealed a more northern distribution for this boreal species than previously reported. We investigated an Arctic fjord to determine if local reproduction is taking place. Combining time series data from depth stratified sampling with molecular tools for species identification, we found C. helgolandicus from all stages throughout the year including males and females as well as a nauplius. These findings constitute strong evidence that C. helgolandicus is reproducing north of the Arctic Circle and their role in the ecosystem should be investigated further.